A THEORETICAL ANALYSIS OF THE SUBROGATION, AS PER THE AMENDMENTS BROUGHT BY THE CIVIL CODE OF 2009 - GABRIEL BOROI; BOGDAN NAZAT (Challenges of the Knowledge Society)
Although extensively treated by the Romanian scholars in the past, the provisions of the Civil code of 2009 brought certain amendments with respect to the subrogation in creditor’s rights by paying the debt. Our main purpose is to outline the latest amendments brought to the institution under discussion by the Civil Code of 2009 and, in this respect, we will analyse the subrogation from a theoretical point of view, with some references to the existent Romanian jurisprudence.